Caspase-8 Inhibition Prevents the Cleavage and Degradation of E3 Ligase Substrate Receptor Cereblon and Potentiates Its Biological Function - Zhou, Liang; Yu, Wenjun; Jayabalan, David S.; Niesvizky, Ruben; Jaffrey, Samie R.; Huang, Xiangao; Xu, Guoqiang (Frontiers in Cell and Developmental Biology, 2020)
Cereblon (CRBN), a substrate receptor of cullin 4-RING E3 ligase (CRL4), mediates the ubiquitination and degradation of constitutive substrates and immunomodulatory drug-induced neo-substrates including MEIS2, c-Jun, CLC1, IKZF1/3, CK1, and SALL4. It has been reported that CRBN itself could be degraded through the ubiquitin-proteasome system by its associated or other cullin-RING E3 ligases, thus modulating its biological functions. However, it is unknown whether the CRBN stability and its biological function could be modulated by caspases. In this study, using model cell lines, we found that activation of the death receptor using tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) leads to the decreased CRBN protein level. Through pharmacological inhibition and activation of caspase-8 (CASP-8), we disclosed that CASP-8 regulates CRBN cleavage in cell lines. Site mapping experiments revealed that CRBN is cleaved after Asp9 upon CASP-8 activation, resulting in the reduced stability. Using myeloma as a model system, we further revealed that either inhibition or genetic depletion of CASP-8 enhances the anti-myeloma activity of lenalidomide by impairing CRBN cleavage, leading to the attenuated IKZF1 and IKZF3 protein level and the reduced viability of myeloma cell lines and primary myeloma cells from patients. The present study discovered that the stability of the substrate receptor of a E3 ligase can be modulated by CASP-8 and suggested that administration of CASP-8 inhibitors enhances the overall effectiveness of lenalidomide-based combination therapy in myeloma.